RICERCA È SVILUPPO 2020 - Pages, Content (International Multidisciplinary Research Journal, 2020)
Background, Research gap and Objective This conference takes up the ambitious challenge of highlighting the positive exchange between scientific knowledge. Even if the Academy is characterized by disciplinary specialization, only rarely analysis and application developments do not need other forms of knowledge or do not involve other scientifically qualified context. Have approved both research works developed by multidisciplinary groups and sectoral works that considered further studies, scenarios and application cases with a multidisciplinary development.